2022
DOI: 10.1186/s12959-022-00403-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictive ability of viscoelastic testing using ClotPro® for short-term outcome in patients with severe Covid-19 ARDS with or without ECMO therapy: a retrospective study

Abstract: Background SARS-CoV-2 infections are suspected to trigger the coagulation system through various pathways leading to a high incidence of thromboembolic complications, hypercoagulation and impaired fibrinolytic capacity were previously identified as potentially mechanisms. A reliable diagnostic tool for detecting both is still under discussion. This retrospective study is aimed to examine the prognostic relevance of early viscoelastic testing compared to conventional laboratory tests in COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 84 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…Existing transfusion algorithms provide cutoffs for ROTEM ® parameters to guide the substitution of blood products and coagulation factor concentrates [26,27]. ClotPro ® is a relatively new device that is increasingly being used in Europe and worldwide [16,18,[28][29][30][31]. In current clinical practice, ClotPro ® viscoelastic hemostatic assays have been used, but therapeutic consequences continue to be deduced from established algorithms based on ROTEM ® or TEG parameters [11,12,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Existing transfusion algorithms provide cutoffs for ROTEM ® parameters to guide the substitution of blood products and coagulation factor concentrates [26,27]. ClotPro ® is a relatively new device that is increasingly being used in Europe and worldwide [16,18,[28][29][30][31]. In current clinical practice, ClotPro ® viscoelastic hemostatic assays have been used, but therapeutic consequences continue to be deduced from established algorithms based on ROTEM ® or TEG parameters [11,12,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Their findings were strengthened by a study conducted by Wright and colleagues who reported that combination of high D-dimer levels and hypofibrinolysis indicated by VET showed the best predictive value for thrombotic events and renal failure [ 4 ]. In 2022, Heubner and colleagues reported that VET may predict the severity of disease, and might be useful in detecting impaired fibrinolysis in patient with COVID-19-associated ARDS [ 22 ], hence there is some rationale to utilize point-of-care VET in daily practice in order to manage CAC appropriately [ 23 ]. In 2021, Wang et al developed a practical TEG-based anticoagulation algorithm to screen and identify patients at high risk for both thrombotic and bleeding complications and to guide their management [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In ClotPro ® , viscoelastic assays can be used to assess hypercoagulability. In patients with COVID-19, various groups have noted a shorter time for clot generation (CT), elevated fibrinogen concentration and function (A10), increased maximum clot firmness (MCF), and increased clot stability [ 31 ]. Many researchers performed viscoelastic tests on patients with COVID-19 in studies that enrolled only 20–50 patients.…”
Section: Discussionmentioning
confidence: 99%